El proceso de enseñanza-aprendizaje de Lengua y Literatura - Villafuerte Villafuerte, Ana Paola (2022)
he present investigation was oriented to solve the following problem: What didactic strategies of reading and writing can be used in the teaching-learning process of Language and Literature of the students of the Second year of Basic General Education of the Fiscal Educational Unit "Dr. . Ricardo Cornejo Rosales" from the parish of Guamani in the city of Quito, his priority was to develop his skills through strategies that allow him to strengthen his knowledge through didactic activities and thus have meaningful learning. The Didactic Guide for the development of linguistic awareness favored the process of reading and writing of the students, directed at teachers because it is a scientific, unique and novel instrument, since it guides the teacher to work in a more didactic way, using methods that allow enhance their knowledge, where the teacher is the facilitator of learning. This research sought to demonstrate the importance of reading and writing in students, being the basis of a quality education, this allowed through the diagnosis of the problem investigated, for the organization and selection of contents of the guide is based on the results of the diagnosis. The methodology was based on the pragmatic paradigm, its approach was mixed, the methods used were the analytical-synthetic method, the deductive and inductive methods, the modeling method and the techniques used were the observation, interview and survey forms to evidence the work done by teachers in the teaching-learning process, for the purpose of making improvements from the design of the proposal. For the development of the guides, existing methods were taken into account, using methodological strategies that respond to the needs of students and teachers, obtaining great results in the process.